2003
DOI: 10.1186/1471-2156-4-13
|View full text |Cite
|
Sign up to set email alerts
|

Study of human SP-A, SP-B and SP-D loci: allele frequencies, linkage disequilibrium and heterozygosity in different races and ethnic groups

Abstract: Background: SP-A, SP-B, and SP-D are pulmonary surfactant proteins. Several linkage and association studies have been done using these genes as markers to locate pulmonary disease susceptibility genes, but few have studied the markers systematically in different ethnic groups. Here we studied eight markers in SP-A, SP-B, and SP-D genes in seven ethnic groups from three races (Caucasian, Black and Hispanic). We measured the similarity of the marker distribution among the ethnic groups in order to see whether pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…This might be attributed either to ethnic differences between the studied population and individuals analyzed in other countries, or to sample size. Liu et al (32) have reported that ethnic background is an important risk factor to be considered in analytical studies of allele and genotype frequencies. These investigators analyzed Surfactant protein B gene and respiratory distress syndrome www.bjournal.com.br the similarity of genetic markers among populations of three different ethnic groups (Caucasian, Black, and Hispanic) in order to determine whether individuals of different races or ethnic groups could be grouped together in linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed either to ethnic differences between the studied population and individuals analyzed in other countries, or to sample size. Liu et al (32) have reported that ethnic background is an important risk factor to be considered in analytical studies of allele and genotype frequencies. These investigators analyzed Surfactant protein B gene and respiratory distress syndrome www.bjournal.com.br the similarity of genetic markers among populations of three different ethnic groups (Caucasian, Black, and Hispanic) in order to determine whether individuals of different races or ethnic groups could be grouped together in linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…They analyzed the similarity of genetic markers among populations of three different ethnic groups (Caucasian, Black, and Hispanic), in order to observe whether individuals of different races or ethnic groups could be grouped together in linkage studies. The results showed that the allele and genotype frequencies can differ between distinct ethnic groups, especially between ethnic groups of different races (32).…”
Section: Discussionmentioning
confidence: 98%
“…Liu et al (32) have reported that ethnic background is an important risk factor in analytical studies of allele and genotype frequencies. They analyzed the similarity of genetic markers among populations of three different ethnic groups (Caucasian, Black, and Hispanic), in order to observe whether individuals of different races or ethnic groups could be grouped together in linkage studies.…”
Section: Discussionmentioning
confidence: 99%
“…The polymorphism C/A(1013) did show an association with the amounts of SP-B, with the CC individuals having significantly less SP-B than the heterozygotes or those homozygous for the A allele. It is known that C/A(Ϫ18) is in linkage disequilibrium with C/A(1013), with the A allele of C/A(Ϫ18) linked to the C allele of C/A(1013) (17). It is probable that the association of SP-B concentrations with C/A(1013) is due to the linkage of the polymorphism to C/A(Ϫ18); however, a contribution of C/A(1013) to SP-B protein levels cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%